2018
DOI: 10.1007/s40258-018-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Tuberculosis Diagnosis in Cambodia with and without Xpert® MTB/RIF for People Living with HIV/AIDS and People with Presumptive Multidrug-resistant Tuberculosis

Abstract: Xpert test unit costs could be reduced through lower cartridge prices, longer usable life of GeneXpert (Cepheid, USA) instruments, and increased test volumes; however, epidemiological and test eligibility conditions in Cambodia limit the number of specimens received at laboratories, leading to sub-optimal utilization of current instruments. Improvements to patient referral and specimen transport could increase test volumes and reduce Xpert test unit costs in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…To assess validity of our unit cost estimates, we compared our results with previously published estimates of TB diagnostics and interventions. [16,[24][25][26][27] Focusing on cost per Xpert test, we find our estimates consistent and comparable to the existing evidence (between $12 and $42 per test) factoring operational settings, costing methods, consumables costs, and testing volumes. In comparing our cost per program yield estimates, we found one study that reported costs of program operation and yields of the CATA program that overleaped with our assessment period but reporting much lower cost estimate.…”
Section: Discussionsupporting
confidence: 82%
“…To assess validity of our unit cost estimates, we compared our results with previously published estimates of TB diagnostics and interventions. [16,[24][25][26][27] Focusing on cost per Xpert test, we find our estimates consistent and comparable to the existing evidence (between $12 and $42 per test) factoring operational settings, costing methods, consumables costs, and testing volumes. In comparing our cost per program yield estimates, we found one study that reported costs of program operation and yields of the CATA program that overleaped with our assessment period but reporting much lower cost estimate.…”
Section: Discussionsupporting
confidence: 82%
“…As health system costs were not included in the program costing, we used primary cost data on personnel and diagnostics collected in 2014 ( Table 1 and Supplementary Table S1 ) to estimate costs incurred at the health facilities [ 18 ]. The costs per test or procedure were computed based on the number of people with presumptive TB referred to the health facilities and the number of tests conducted.…”
Section: Methodsmentioning
confidence: 99%
“…The costs per test or procedure were computed based on the number of people with presumptive TB referred to the health facilities and the number of tests conducted. We also included the cost of treatment/community directly observed treatment, short course (C-DOTS) reported in 2014 [ 18 ]. TB treatment was initiated and managed by the public health facilities regardless of the mode of case-finding strategies.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are no costing studies on CS available for Cambodia. A few studies assessed the cost of specific health care services or diseases (e.g., [10][11][12][13]). The latest published costing study assessed the unit costs of public health care services in several health centres and hospitals using a step down costing approach [13].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies assessed the cost of specific health care services or diseases (e.g., [10][11][12][13]). The latest published costing study assessed the unit costs of public health care services in several health centres and hospitals using a step down costing approach [13]. While it showed that costing was feasible with this methodology, the study can only inform about the costs of certain units like outpatient visits or inpatient days at certain departments.…”
Section: Introductionmentioning
confidence: 99%